2020
DOI: 10.1111/ppc.12554
|View full text |Cite
|
Sign up to set email alerts
|

The effect of a solution‐oriented approach in depressive patients on social functioning levels and suicide probability

Abstract: Purpose: This study was conducted to evaluate the effect of a solution-oriented approach in depressive patients on suicide probability and the social functioning level. Design and Method: The research was designed as a randomized controlled trial with a pretest and posttest control group and repeated measures. A Solution-Oriented Approach Intervention (SOAI) was performed for a total of 6 to 10 sessions with the experimental group. Findings: The SOAI in depressive patients effectively increased the social func… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 43 publications
(84 reference statements)
0
11
0
Order By: Relevance
“…In assessment of RCTs, overall risk of bias was low in 9 studies, 31 45 48 50 54 60 61 63 66 moderate in 10 studies 25 33 36 38 49 53 57 59 65 67 and high in 11 studies. 28 34 35 37 41 43 44 46 47 51 62 High and moderate risk of bias ratings were due primarily to concerns about missing outcome data and measurement of the outcome. None of the randomised studies included in this review were found to have high risk of bias in domains related to the randomisation process or selection of reported results.…”
Section: Resultsmentioning
confidence: 99%
“…In assessment of RCTs, overall risk of bias was low in 9 studies, 31 45 48 50 54 60 61 63 66 moderate in 10 studies 25 33 36 38 49 53 57 59 65 67 and high in 11 studies. 28 34 35 37 41 43 44 46 47 51 62 High and moderate risk of bias ratings were due primarily to concerns about missing outcome data and measurement of the outcome. None of the randomised studies included in this review were found to have high risk of bias in domains related to the randomisation process or selection of reported results.…”
Section: Resultsmentioning
confidence: 99%
“…The effectiveness of SFBT in literature has been evaluated in many studies. 14,24,[38][39][40] Studies have shown that SFBT is effective in individuals with social anxiety disorder, 13 reduces depression and anxiety, 12,15 improves quality of life 14 , affects mindfulness and psychological well-being 41 and is effective in solving mental problems by contributing to the development of all areas of mental health. 40 In the study conducted by Novella, Ng and Samuolis, SFBT was applied to university students with mild and moderate anxiety simultaneously with two different methods using face-to-face and online programmes.…”
Section: Discussionmentioning
confidence: 99%
“…13,14 Focusing on the solution can increase the self-confidence of individuals, their capacity to produce solutions, and their ability to see their strengths and positive aspects. 15 It is reported in the literature that short-term therapies provide faster benefits than long-term psychotherapies. For this reason, it is thought that short-term therapies will be applied in a short time and have a rapid effect in reducing the anxiety of parents during the pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…The effectiveness of SFSP in literature has been evaluated in many studies. 17 , 28 , 29 , 41 , 42 Studies have shown that SFSP is effective in individuals with social anxiety disorder, 16 reduces depression and anxiety, 15 , 18 improves quality of life, 17 affects mindfulness and psychological well‐being 43 and is effective in solving mental problems by contributing to the development of all areas of mental health. 42 In the study conducted by Novella et al, SFSP was applied to university students with mild and moderate anxiety simultaneously with two different methods using face‐to‐face and online programmes.…”
Section: Discussionmentioning
confidence: 99%
“…16 , 17 Focusing on the solution can increase the self‐confidence of individuals, their capacity to produce solutions, and their ability to see their strengths and positive aspects. 18 It is reported in the literature that short‐term therapies provide faster benefits than long‐term psychotherapies. 19 For this reason, it is thought that short‐term therapies will be applied in a short time and have a rapid effect in reducing the anxiety of parents during the pandemic.…”
Section: Introductionmentioning
confidence: 99%